2004
DOI: 10.1046/j.1529-8817.2003.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Human Stature in a Large Sample of Multiplex Pedigrees

Abstract: SummaryRecently, we reported a whole genome scan on a sample of 630 Caucasian subjects from 53 human pedigrees. Several genomic regions were suggested to be linked to height. In an attempt to confirm the identified genomic regions, as well as to identify new genomic regions linked to height, we conducted a whole genome linkage study on an extended sample of 1,816 subjects from 79 pedigrees, which includes the 53 pedigrees containing the original 630 subjects from our previous whole genome study and an addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
3

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 63 publications
1
28
3
Order By: Relevance
“…In conclusion, our results illustrate how high-resolution genomic microarrays facilitate the high-resolution delineation of breakpoint regions and provide a strong argument for the more widespread adoption of microarray analysis for systematic characterisation of genome rearrangements associated with human syndromes. Noticeably, a recent study, aiming to identify genomic regions linked to height through a whole genome scan, showed the highest multipoint LOD score (2.74) on chromosome 9 with the marker D9S287, 21 which is deleted in both patients in our study. The common region deleted in both patients encompasses 56 Ensembl predicted genes, two of which are of particular interest.…”
mentioning
confidence: 78%
“…In conclusion, our results illustrate how high-resolution genomic microarrays facilitate the high-resolution delineation of breakpoint regions and provide a strong argument for the more widespread adoption of microarray analysis for systematic characterisation of genome rearrangements associated with human syndromes. Noticeably, a recent study, aiming to identify genomic regions linked to height through a whole genome scan, showed the highest multipoint LOD score (2.74) on chromosome 9 with the marker D9S287, 21 which is deleted in both patients in our study. The common region deleted in both patients encompasses 56 Ensembl predicted genes, two of which are of particular interest.…”
mentioning
confidence: 78%
“…Genetic studies using association or whole genome linkage approaches have suggested quite a few genes and genomic regions associated with or linked to human height (Beck et al 2003;Geller et al 2003;Sammalisto et al 2005;Garnero et al 1998;Hasegawa et al 2000;Perola et al 2001;Hirschhorn et al 2001;Deng et al 2002;Liu et al 2004). However, few such genes and genomic regions Electronic Supplementary Material Supplementary material is available for this article at http://dx.doi.org/10.1007/s00439-006-0136-y and is accessible for authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was performed on a sample greatly extended from those for our previous two consecutive whole genome linkage studies on human height (Deng et al 2002;Liu et al 2004). The sample size has increased from 630 in our initial whole genome study (WG1 study) (Deng et al 2002) to 1,816 in our second one (WG2 study) , and from that to the present 3,726 subjects, the largest sample ever obtained from a single study population of the same ethnicity in the field of linkage studies of human complex traits.…”
Section: Introductionmentioning
confidence: 99%
“…This region and its flanking regions have previously been reported as linked to height in different populations. Perola et al (2001) reported a QTL for height with a maximum LOD score of 2.61 located telomeric of our findings at 9q34, and Liu et al (2004) reported three loci of interest on the long arm of chromosome 9. Their highest linkage peak (LOD score 2.74, p = 0.0003) was detected on 9q22.…”
Section: Susceptibility Loci For Adult Heightmentioning
confidence: 99%
“…These fairly low power estimates suggest that additional chromosome regions not detected in the current study might be of great importance for variation in adult height in the studied population. Since the first genome-wide linkage scans for height were performed in 2001 (Hirschhorn et al 2001;Perola et al 2001), several susceptibility loci for height have been reported [for a recent overview see Perola et al (2007)], but, as for most complex phenotypes, only some have been successfully replicated by further studies (Liu et al 2004(Liu et al , 2006Willemsen et al 2004;Sale et al 2005;Shmulewitz et al 2006). The most promising susceptibility loci for height (Score.Max p = 0.005) detected in our current study of sib-pairs from American Samoa was located on chromosome 9q31 at marker D9S1690.…”
Section: Susceptibility Loci For Adult Heightmentioning
confidence: 99%